2000
DOI: 10.1099/0022-1317-81-5-1165
|View full text |Cite
|
Sign up to set email alerts
|

High genetic variability of the group-specific a-determinant of hepatitis B virus surface antigen (HBsAg) and the corresponding fragment of the viral polymerase in chronic virus carriers lacking detectable HBsAg in serum

Abstract: Chronic carriers of hepatitis B virus (HBV) usually show hepatitis B surface antigen (HBsAg) in their sera, which is considered the best marker for acute and chronic HBV infection. In some individuals, however, this antigen cannot be detected by routine serological assays despite the presence of virus in liver and peripheral blood. One reason for this lack of HBsAg might be mutations in the part of the molecule recognized by specific antibodies. To test this hypothesis, the HBV S gene sequences were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
2
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(173 citation statements)
references
References 39 publications
7
158
2
6
Order By: Relevance
“…It has been suggested that increased frequency of mutations in MHL region might contribute to immune escape and occult infection [Weinberger et al, 2000]. Substitutions in the MHL region possibly caused structural changes that contributed to failure of HBsAg detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that increased frequency of mutations in MHL region might contribute to immune escape and occult infection [Weinberger et al, 2000]. Substitutions in the MHL region possibly caused structural changes that contributed to failure of HBsAg detection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the major hydrophilic loop (MHL) of the S gene region of HBsAg negative virus carriers exhibits almost exactly three times as many amino acid exchanges in comparison to the HBsAg positive virus carriers [Weinberger et al, 2000]. This underscores the role of S gene mutations in case of occult infection.…”
Section: Introductionmentioning
confidence: 99%
“…7 Any mutation in the pre-S and surface regions may alter HBsAg antigenicity and inhibit anti-HBs production. For example, a single mutation at the ''a'' determinant (amino acid 124-147) of HBsAg can lead to a change in the immunologic epitope, 19,33,34 and mutations or deletion in the pre-S gene can inhibit HBsAg secretion. 35 In addition, because of overlapping of the HBV surface and polymerase genes, the surface gene mutations also caused amino acid mutation in the RT domain of polymerase gene.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] However, the results of these studies have been inconsistent, and some show that most occult HBV are caused by wild-type strains. 7,8,22 Further case control studies are needed to investigate pre-S and surface gene mutations to clarify the absence of detectable HBsAg.…”
mentioning
confidence: 99%
“…Mutations in the PreS and S sequences have also been reported in HBsAg-negative subjects as possibly affecting other domains of the viral envelope. [35][36][37] Two studies have suggested that different HBV genotypes might be detected in patients with or without detectable serum HBsAg. 37,38 Still, despite the considerable interest of these observations, it is important to note that only a few investigations [39][40][41] provided a complete genome sequence analysis, so that the impact of such mutations on the serologic profile has not been assayed in a completely relevant context.…”
Section: What Is the Molecular Basis Of Hbv Persistence In Hbsag-negamentioning
confidence: 99%